Macroprudential Stress Tests : A Reduced-Form Approach to Quantifying Systemic Risk Losses - Alla, Zineddine (IMF Working Papers; Working Paper ;, 2018)
We present a novel approach that incorporates individual entity stress testing and losses from systemic risk effects (SE losses) into macroprudential stress testing. SE losses are measured using a reduced-form model to value financial entity assets, conditional on macroeconomic stress and the distress of other entities in the system. This valuation is made possible by a multivariate density which characterizes the asset values of the financial entities making up the system. In this paper this density is estimated using CIMDO, a statistical approach, which infers densities that are consistent with entities' probabilities of default, which in this case are estimated using market-based data. Hence, SE losses capture the effects of interconnectedness structures that are consistent with markets' perceptions of risk. We then show how SE losses can be decomposed into the likelihood of distress and the magnitude of losses, thereby quantifying the contribution of specific entities to systemic contagion. To illustrate the approach, we quantify SE losses due to Lehman Brothers' default.